Odpowiedzi

  • Użytkownik Zadane
2010-03-20T09:19:28+01:00
T = 2π * √(l/g)

Po przekształceniach:
l = T² * g/4π²

Przed wydłużeniem:
l = 0.6² * 10/4π² = 0.9/π²

Po:
l = 0.9² * 10/4π² = 2.025/π²

Δl = 2.025/π² - 0.9/π² = 1.125/π² ≈ 0.113986 [m]
Najlepsza Odpowiedź!
2010-03-20T09:20:20+01:00
Dane:
T₁ = 0,6s
T₂ = 0,9s
g = 10 [m/s²]
Rozw.:

T = 2π √l/g
z tego liczymy l
T² = 4π²l/g
T²g = 4π²l
l₁ = T₁²g / 4π² = (0,6s)² × 10 [m/s²] / 4×(3,14)² = 0,09 m
l₂ = T₂²g / 4π² = (0,9s)² × 10 [m/s²] / 4×(3,14)² =0,205 m
Δl = l₂ - l₁ = 0,205m - 0,09m = 0,115 m